Novel erythropoietin-based therapeutic candidates with extra N-glycan sites that block hematopoiesis but preserve neuroplasticity - Bürgi Fissolo, María de Los Milagros (2021)
Neurological disorders affect millions of people causing behavior-cognitive disabilities. Nowadays they have no effective treatment. Human erythropoietin (hEPO) has been clinically used because of its neurotrophic and cytoprotective properties. However, the erythropoietic activity (EA) should be considered as a side effect. Some analogs like non-sialylated EPO, carbamylated EPO, or EPO peptides have been developed showing different weaknesses: erythropoiesis preservation, low stability, potential immunogenicity, or fast clearance. Herein, we used a novel strategy that blocks the EA but preserves hEPO neurobiological actions. N-glycoengineering was accomplished to add a new glycosylation site within the hEPO sequence responsible for its EA. hEPO-derivatives were produced by CHO.K1 cells, affinity-purified and functionally analyzed studying their in vitro and in vivo EA, their in vitro neuronal plasticity in hippocampal neurons and their neuroprotective action by rescuing hippocampal neurons from apoptosis. Muteins Mut 45_47 (K45 > N45 + N47 > T47), Mut 104 (S104 > N104), and Mut 151_153 (G151 > N151 + K153 > T153) lost their EA but preserved their neuroprotection activity and enhanced neuroplasticity more efficiently than hEPO. Interestingly, Mut 45_47 resulted in a promising candidate to explore as neurotherapeutic considering not only its biopotency but also its pharmacokinetic potential due to the hyperglycosylation.